Resection of synchronous ipsilateral giant bullae and bronchial carcinoid tumor - YILDIZELİ, BEDRETTİN; BATIREL, HASAN FEVZİ; BOSTANCI, KORKUT (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Synchronous bronchial carcinoid tumor and giant bullae are rare entities. In this article, we report a 62-year-old male presenting with dyspnea, cough and chest pain. No improvement was achieved with medical treatment. Examinations revealed right lower lobe endobronchial carcinoid tumor and upper lobe giant bullae. Simultaneous bullectomy and bronchotomy and carcinoid tumor resection through right thoracotomy, as well as postoperative tracheostomy were performed. The patient who had 2 lt/minute oxygen was discharged on the 16th postoperative day without any complication. Radiological, apprearance, clinical situation and pulmonary functions were improved and better quality of life was observed at six months after surgery. Forced expiratory volume in 1 second (FEV1) increased from 0.90 liter (29% predicted) to 1.13 liter (37% predicted). Patient continued to smoke and died due to cor pulmonale one year after discharge.
Keywords: Bronchotomy; bullae; bullectomy; endobronchial carcinoid; EMPHYSEMA